2014
DOI: 10.1038/onc.2014.163
|View full text |Cite
|
Sign up to set email alerts
|

Src kinase function controls progenitor cell pools during regeneration and tumor onset in the Drosophila intestine

Abstract: Src non-receptor kinases have been implicated in events late in tumor progression. Here, we study the role of Src kinases in the Drosophila intestinal stem cell (ISC) lineage, during tissue homeostasis and tumor onset. The adult Drosophila intestine contains only two progenitor cell types, division-capable ISCs and their daughters, postmitotic enteroblasts (EBs). We found that Drosophila Src42a and Src64b were required for optimal regenerative ISC division. Conversely, activation of Src42a, Src64b or another n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 99 publications
8
54
0
Order By: Relevance
“…Experiments in which we simultaneously over‐expressed Ret and downregulated Src42A or Src64B (the two Src kinases in Drosophila ) from adult intestinal progenitors confirmed that Src42A , but not Src64B , is required for both Ret ‐driven hyperplasia and activation of Wg ligand in intestinal progenitors (Fig 4C). The existence of positive feedback between Ret and Wg pathways via Src42A was further suggested by the fact that activation of Src42A upregulated Wg ligand in intestinal progenitors (Fig 4D), and by our finding that the previously reported proliferation increase resulting from Src42A activation (Cordero et al , 2014; Kohlmaier et al , 2015) was, at least partially, Ret ‐dependent (Fig 4E).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…Experiments in which we simultaneously over‐expressed Ret and downregulated Src42A or Src64B (the two Src kinases in Drosophila ) from adult intestinal progenitors confirmed that Src42A , but not Src64B , is required for both Ret ‐driven hyperplasia and activation of Wg ligand in intestinal progenitors (Fig 4C). The existence of positive feedback between Ret and Wg pathways via Src42A was further suggested by the fact that activation of Src42A upregulated Wg ligand in intestinal progenitors (Fig 4D), and by our finding that the previously reported proliferation increase resulting from Src42A activation (Cordero et al , 2014; Kohlmaier et al , 2015) was, at least partially, Ret ‐dependent (Fig 4E).…”
Section: Resultssupporting
confidence: 69%
“…Consistent with this biochemical interaction, we observed that, in addition to upregulating Wg, Ret over‐expression in adult intestinal progenitors also resulted in enhanced phospho‐Src immunoreactivity (Fig 4B), suggestive of Src kinase activation. Activation of Src cytoplasmic tyrosine kinases is frequently implicated in signal transduction downstream of transmembrane receptors, and modulation of Src levels in intestinal progenitors results in phenotypes similar to those described above for Ret depletion/over‐expression (Cordero et al , 2014; Kohlmaier et al , 2015), suggesting that Ret‐induced hyperproliferation may require Src kinases. Experiments in which we simultaneously over‐expressed Ret and downregulated Src42A or Src64B (the two Src kinases in Drosophila ) from adult intestinal progenitors confirmed that Src42A , but not Src64B , is required for both Ret ‐driven hyperplasia and activation of Wg ligand in intestinal progenitors (Fig 4C).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…For example, Drosophila simple columnar epithelia such as imaginal discs rely primarily on apical Crb-Mer/Ex-Kibra-Sav signalling to retain Yki in the cytoplasm and restrict tissue growth (Baumgartner et al, 2010;Chen et al, 2010;Genevet et al, 2010;Hamaratoglu et al, 2006;Ling et al, 2010;Yu et al, 2010). By contrast, Drosophila stratified columnar epithelia such as the intestine require integrins, Src, EGFR and Yki to promote proliferation of basal layer stem/progenitor cells, suggesting that the regulatory connection between them described here is also conserved (Cordero et al, 2014;Jiang et al, 2011;Kohlmaier et al, 2015;Lin et al, 2013;Shaw et al, 2010;Staley and Irvine, 2010;Xu et al, 2011). Furthermore, ectopic activation of Src, EGFR, PI3K or Yki in simple columnar imaginal discs is sufficient to induce overproliferation of cells, whereas loss of PI3K or Yki strongly impairs imaginal disc tumour formation (Doggett et al, 2011;Enomoto and Igaki, 2013;Fernandez et al, 2014;Herranz et al, 2012Herranz et al, , 2014Strassburger et al, 2012;Willecke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To confirm these TS-MARCM results, we used a second method for distinguishing symmetric from asymmetric ISC divisions in homozygous control or lin-28 Δ1 mutant intestines (Kohlmaier et al, 2015). In this approach, a GFP-tagged version of the localization domain of Partner of Numb (Pon::GFP) was expressed specifically in ISCs.…”
Section: Lin-28 Promotes Isc Symmetric Renewalmentioning
confidence: 99%